A method for preparing a UIO-66 derived porous carbon material organic composite aerogel adsorbent
By thiol-modified UIO-66 porous carbon material and composited with organic polymer, a three-dimensional porous composite aerogel adsorption material was prepared, which solved the problem of unstable MOF in harsh environments and small particle size of porous carbon material, and achieved efficient mercury ion adsorption and reusable material.
Patent Information
- Application Number
- CN202411929933.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
The existing MOF is unstable in water environments and harsh environments such as acids and alkalis, resulting in limitations in water treatment applications. The particle size of the porous carbon materials derived from MOF is small, difficult to fix and separate, and easy to cause secondary pollution.
By modifying the UIO-66 porous derivatized carbon material and compounding it with organic polymer, a three-dimensional porous composite aerogel adsorption material is prepared, and functional groups such as amino groups and sulfhydryl groups are introduced to improve the selective adsorption of mercury ions, and the mechanical strength and reusability are improved through the three-dimensional porous network structure.
It realizes efficient selective adsorption of mercury ions, improves the mechanical properties and reusability of adsorbents, and solves the problem that materials are not easy to recover and reuse during water treatment.
Smart Images

Figure CN119733483A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and specifically relates to a method for preparing a UIO-66 derived porous carbon material organic composite aerogel adsorbent. Background Art
[0002] In daily life, mercury is widely used in glass mercury thermometers, batteries, fluorescent lamps, pigments, pesticides and chemical catalysts. However, when people handle mercury-containing products, improper handling can easily lead to serious mercury pollution. Inorganic mercury ions in the environment can easily produce methylmercury, which poses a threat to humans and ecosystems. Therefore, it is urgent to propose some practical methods to remove mercury pollutants from the environment, especially in water media. The commonly used methods currently include: chemical precipitation, biological treatment, ion exchange, membrane separation and adsorption. Among them, the adsorption method is considered to be one of the most competitive methods for removing mercury pollutants due to its simple operation, large processing capacity, high removal efficiency and no need for complex equipment.
[0003] In recent years, metal organic frameworks (MOFs) have attracted extensive attention due to their porous crystal structure, adjustable surface functions and sufficient active adsorption sites. Among them, UiO-66-NH2 modified with thiourea, isothiocyanate and isocyanate has good adsorption properties for heavy metal ions (Microporous and Mesoporous Materia1s 2016, 221: 238-244.). However, since MOF is unstable in water environment and in harsh environments such as acid and alkali, its application in water treatment is limited (Nature Reviews Materials 2016, 1 (3): 727-729.). Due to the high carbon content of the organic components in MOF, it is easy to obtain a porous carbon structure after treatment, and no other carbon precursors are required, avoiding the cumbersome, expensive and environmentally harmful synthesis process. In addition to inheriting the characteristics of its regular and ordered pore structure, the porous material obtained by direct carbonization of MOF also has stronger chemical stability and has a wide range of applications in the fields of environment and energy. However, the main limitation of MOF-derived porous carbon materials in adsorption applications is that the materials are usually powders or crystals with very small particle sizes (Separation and Purification Technology 2024, 343: 127169), which makes them difficult to fix and separate during the adsorption process, and even easily causes secondary pollution.
[0004] The composite material of the present invention is obtained by modifying the UIO-66 porous derivative carbon material with thiol groups and then compounding it with an organic polymer to obtain a three-dimensional porous composite aerogel adsorption material. By introducing functional groups such as amino groups and thiol groups, the composite aerogel exhibits excellent selective adsorption of mercury ions. In addition, the construction of the three-dimensional porous network structure makes the aerogel adsorbent have high mechanical strength, easy recovery and reusability. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a method for preparing a UiO-66-derived porous carbon material / organic composite aerogel adsorbent. In order to solve the problems such as poor stability of MOF in water environment and harsh environments such as acid and alkali, and to achieve efficient adsorption of mercury ion pollutants, the present invention pyrolyzes and carbonizes the MOF material to obtain a porous material that inherits the regular and orderly pore structure characteristics of MOF, and effectively enhances the selective adsorption of mercury ions by introducing functional groups such as thiol.
[0006] Since MOF-derived carbon materials generally exist in powder form, they are difficult to recycle and have poor reusability during water treatment. The present invention utilizes organic porous aerogel to load UIO-66-derived porous carbon materials, which further improves the adsorption and mechanical strength of the material, while achieving the recovery and reuse of the adsorbent.
[0007] The technical solution adopted by the present invention is:
[0008] The present invention provides a method for preparing a UIO-66 derived porous carbon material organic composite aerogel adsorbent, comprising the following steps:
[0009] Step (1) adding a zirconium-containing soluble salt to an organic solvent I containing 2,5-diaminoterephthalic acid and an acidic pH regulator, mixing and transferring the mixture into a polytetrafluoroethylene-lined reactor. After reaction, separation, washing and drying, UiO-66-NH 2 powder.
[0010] Step (2) UiO-66-NH obtained in step (1) 2 The powder is subjected to segmented pyrolysis and carbonization to obtain porous carbon material I.
[0011] Step (3) The porous carbon material I obtained in step (2) is soaked in hydrofluoric acid, centrifuged, and washed to obtain porous carbon material II.
[0012] Step (4) Mix the porous carbon material II obtained in step (3) with an organic solvent II containing a mercapto-modified material and N-N-dimethylformamide (DMF), react, separate, wash, precipitate, and dry to obtain an adsorbent material I;
[0013] Step (5) dispersing the organic aerogel precursor in deionized water and modifying it with an acidic pH regulator to obtain a mixed solution I;
[0014] Step (6) adding the adsorbent material I obtained in step (4) to the mixed solution I and stirring evenly to obtain a mixed solution II;
[0015] Step (7) dropping the mixed solution II into a calcium chloride solution, cross-linking at room temperature, then washing with water, and freeze-casting to obtain a UiO-66 derived porous carbon material / organic composite aerogel.
[0016] Preferably, the reaction conditions in step (1) are: heating at 100°C for 24 hours, filtering the solid product after cooling to room temperature; washing with NN dimethylformamide (DMF) 5 to 6 times; and drying under vacuum at 80°C for 2 hours.
[0017] Preferably, the pyrolysis in step (2) is carried out in a tubular furnace: the pyrolysis conditions are: nitrogen atmosphere, pyrolysis temperature of 400-900° C., and the maximum temperature holding time of 0.5-1 hour.
[0018] Preferably, the immersion time of hydrofluoric acid in step (3) is 6 to 8 hours:
[0019] Preferably, the reaction conditions in step (4) are: heating at 70°C for 24 hours, filtering the solid product after cooling to room temperature, washing three times with deionized water and NN dimethylformamide (DMF), and drying under vacuum at 100°C for 24 hours.
[0020] Preferably, in step (6), the mass ratio of the organic aerogel precursor to the adsorption material I is 1:2 to 8:1, and the stirring time is 10 hours.
[0021] Preferably, the volume ratio of the calcium chloride solution in step (7) to the mixed solution II is 1:1, and the mass fraction of calcium chloride in the calcium chloride solution is 2% to 2.5%.
[0022] Beneficial Effects of the Invention
[0023] (1) The specific surface area of the UIO-66 derived porous carbon material prepared by the present invention is as high as 1500 m 2 / g is much higher than the specific surface area of activated carbon sold on the market. The surface of the modified material is rich in functional groups such as thiol and amino groups, which can achieve efficient selective adsorption of mercury ions.
[0024] (2) The composite aerogel prepared by the present invention is loaded with UIO-66-derived porous carbon materials both inside and on the surface, thereby effectively improving the adsorption capacity of the composite aerogel. At the same time, the three-dimensional porous network structure further improves the adsorption capacity of the aerogel absorbent and enhances its mechanical properties and reusability.
[0025] (3) The composite aerogel prepared by the present invention has the advantages of good biodegradability, simple preparation, strong adsorption capacity, simple separation, strong repeatability, etc., and is used for selective adsorption and removal of mercury pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Flow chart for the preparation of UiO-66 derived porous carbon material / organic composite aerogel.
[0027] Figure 2 It is a comparison chart of the adsorption capacity of mercury ions by UiO-66 derived porous carbon material / organic composite aerogel of different embodiments. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0029] In some embodiments of the present invention, the zirconium source may include, but is not limited to, zirconium oxide, zirconium tetrachloride, zirconium nitrate, zirconium oxychlorate, and the like.
[0030] In some embodiments of the present invention, the mercapto-modified material may be at least one of mercaptoacetic acid, mercaptopropionic acid, mercaptobenzoic acid, mercaptopyridine and 2,5-dimercapto-1,3,4-thiadiazole (DMTD).
[0031] In some embodiments of the present invention, the organic solvent I comprises at least two of N,N-dimethylformamide, N-methylpyrrolidone, N,N-diethylformamide, methanol, and acetic acid.
[0032] In some embodiments of the present invention, the organic solvent II includes at least two of N,N-dimethylformamide, methanol, and deionized water.
[0033] In some embodiments of the present invention, the acidic pH adjuster includes at least one of dilute hydrochloric acid and glacial acetic acid.
[0034] Example 1
[0035] (1) 2.5 mmol ZrCl 4(0.583 g) and 2.5 mmol (0.490 g) of 2,5-diaminoterephthalic acid (NH2-H2BDC) were dissolved in a mixture of 35 mL of DMF and 15 mL of acetic acid. The solution was then heated at 100 ° C for 24 hours and placed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave. After the reaction was completed and cooled to room temperature, the solid product was filtered, washed with water and ethanol six times in sequence, and vacuum dried at 80 ° C to obtain porous carbon material I.
[0036] (2) The porous carbon material I was accurately weighed to 500 mg, placed in a ceramic crucible, and the crucible was transferred to a tube furnace. The pyrolysis conditions were N 2 In an atmosphere, the sample was heated from room temperature to 200°C at a heating rate of 5°C / min and maintained for 30 min, then heated to 600°C at a heating rate of 5°C / min and maintained for 1 hour. Then, it was slowly cooled to room temperature to obtain a black powder.
[0037] (3) Soak in 30% hydrofluoric acid for 6 hours. Separate the black powder by centrifugation, wash with water to neutral pH. After washing, place in a vacuum drying oven and dry at 100°C for 24 hours to obtain porous carbon material II.
[0038] (4) 3.3 g of porous carbon material II, 3.3 g of ammonium carbonate, 15 mL of formaldehyde and 3.3 g of 2,5-dimercapto-1,3,4-thiadiazole (DMTD) were mixed with 150 mL of NN dimethylformamide (DMF) solution. The mixture was reacted at 75 °C for 24 h, then separated and the precipitate was washed 6 times with NN dimethylformamide (DMF) and deionized water. After drying at 80 °C for 24 h, an adsorbent material was obtained, which was marked as adsorbent material I.
[0039] (5) 2.0 g of chitosan powder was dispersed in 20 mL of ultrapure water, and 1 M acetic acid solution was slowly added dropwise to the system to obtain a mixed solution I;
[0040] (6) adding 0.5 g of adsorbent material I and stirring vigorously. After mechanical stirring for 24 hours, 100 mL of uniform mixed solution II was obtained;
[0041] (7) Prepare 100 mL of a 2.5% calcium chloride solution, drop the mixed solution II into 100 mL of the calcium chloride solution using a syringe, and let it react at room temperature for 24 hours until a high-viscosity chitosan gel is formed, and then freeze-dry it at -80°C for 24 hours to obtain a UiO-66-derived porous carbon material / organic composite aerogel.
[0042] Example 2
[0043] The preparation method of UiO-66 derived porous carbon material / organic composite aerogel is the same as that of Example 1, except that 2.0 g of chitosan powder and 1 g of adsorption material I are added.
[0044] Example 3
[0045] The preparation method of UiO-66 derived porous carbon material / organic composite aerogel is the same as that of Example 1, except that 2.0 g of chitosan powder and 2.0 g of adsorption material I are added.
[0046] Example 4
[0047] The preparation method of UiO-66-derived porous carbon material / organic composite aerogel is the same as that of Example 1, except that the UiO-66-NH 2 The powder was calcined in a tube furnace at a maximum temperature of 400 °C.
[0048] Example 5
[0049] The preparation method of UiO-66-derived porous carbon material / organic composite aerogel is the same as that of Example 1, except that the UiO-66-NH 2 The powder was calcined in a tube furnace at a maximum temperature of 900 °C.
[0050] Experimental process: Preparation of mercury ions (Hg 2+ ) solution with a concentration range of 200 to 800 mg / L, adjusted to pH 3, the experiment was carried out in 15 ml of mercury (II) solution, and then the mixture was shaken for 2 hours. For the adsorption kinetics test, after saturation adsorption, the remaining mercury ions (Hg 2+ ) concentration determination.
[0051] Residual Hg 2+ The concentration determination method includes the following steps: filtering the obtained solution and then using inductively coupled plasma atomic emission spectrometry to determine the remaining Hg 2+ The test results are shown in Table 1.
[0052] Table 1
[0053]
[0054] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0055] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a UIO-66 derived porous carbon material organic composite aerogel adsorbent, characterized in that: The method specifically comprises the following steps: (1) adjusting the molar mass ratio of zirconium-containing soluble salt and 2,5-diaminoterephthalic acid to 1:1, adding them to an organic solvent I containing an excess of an acidic pH regulator, mixing, transferring them into a polytetrafluoroethylene-lined reactor for reaction, separating, washing, and drying to obtain UiO-66-NH2 powder; (2) subjecting the UiO-66-NH2 powder obtained in step (1) to segmented pyrolysis and carbonization to obtain porous carbon material I; (3) etching the porous carbon material I obtained in step (2) by immersion etching with excess hydrofluoric acid, centrifuging, and washing to obtain porous carbon material II; (4) mixing the porous carbon material II obtained in step (3) and the organic solvent II containing the mercapto-modified material and N-N-dimethylformamide (DMF) at a molar mass ratio of 1:1.3:181, reacting, separating, washing, precipitating, and drying to obtain the adsorbent material I; (5) dispersing the organic aerogel precursor in deionized water at a molar mass ratio of 1:100, and modifying it with an acidic pH regulator to obtain a mixed solution I; (6) adding the adsorbent material I obtained in step (4) to the mixed solution I and stirring evenly, wherein the mass volume ratio of the adsorbent material I to the mixed solution I is 1:40, to obtain a mixed solution II; (7) The mixed solution II was dropped into a calcium chloride solution at a volume ratio of 1:5, cross-linked at room temperature, then washed with water, and freeze-cast to obtain a UiO-66-derived porous carbon material / organic composite aerogel.
2. The method for preparing a UIO-66 derived porous carbon material organic composite aerogel adsorbent according to claim 1, characterized in that: In step (1), the zirconium source includes but is not limited to zirconium oxide, zirconium tetrachloride, zirconium nitrate, zirconium oxychlorate, etc.
3. The method for preparing a UIO-66 derived porous carbon material organic composite aerogel adsorbent according to claim 1, characterized in that: In step (2), the pyrolysis carbonization is carried out in a tubular furnace, and the pyrolysis conditions are: nitrogen atmosphere, pyrolysis temperature of 300-1000°C, heating rate set to 5°C / min, when the temperature reaches 200°C, keep it for 0-1 hour and then continue to heat up, when the highest temperature is reached, keep it for 0-2 hours, and then naturally drop to room temperature.
4. The method for preparing a UIO-66 derived porous carbon material organic composite aerogel adsorbent according to claim 1, characterized in that: The immersion time of hydrofluoric acid in step (3) is 6 to 12 hours.
5. The method for preparing a UIO-66 derived porous carbon material organic composite aerogel adsorbent according to claim 1, characterized in that: In step (4), the thiol-modified material includes, but is not limited to, at least one of thioglycolic acid, mercaptopropionic acid, mercaptobenzoic acid, mercaptopyridine and 2,5-dimercapto-1,3,4-thiadiazole (DMTD), the organic solvent II includes at least one of N,N-dimethylformamide, N-methylpyrrolidone, N,N-diethylformamide and deionized water, and the mass ratio of the porous material II to the organic solvent II is 1:10 to 1:
50.
6. The method for preparing a UIO-66 derived porous carbon material organic composite aerogel adsorbent according to claim 1, characterized in that: In step (5), the organic aerogel precursor includes, but is not limited to, at least one of chitosan, carboxymethyl chitosan, cellulose and nanocellulose, and the acidic pH regulator includes, but is not limited to, at least one of dilute hydrochloric acid and glacial acetic acid.
7. The method for preparing a UIO-66 derived porous carbon material organic composite aerogel adsorbent according to claim 5, characterized in that: In step (6), the mass ratio of the organic aerogel precursor to the adsorption material I is 1:0 to 2:
3.
8. The method for preparing a UIO-66 derived porous carbon material organic composite aerogel adsorbent according to claim 1, characterized in that: The mass fraction of calcium chloride in the calcium chloride solution in step (7) is 1.5% to 3%.